Sustainable Production of Biofuels through Membrane-Integrated Systems. Issue 3 (2nd July 2020) - Kumar, Ramesh; Ghosh, Alak Kumar; Pal, Parimal
Abstract : Literature on biodiesel production over the last 10 years (2007–2018) has been critically reviewed directing further research toward membrane-based sustainable and green production. The manuscript discusses how biodiesel production strategies have evolved in the recent years through adoption of better feedstock, better catalysts, more efficient reactor technology, and through incorporation of more efficient downstream separation-purification techniques. The review reveals that though transesterification reaction between alcohol and plant oil/animal fats leading to production of biodiesel is simple, the downstream separation and purification of the final product (fatty acid methyl esters) is quite challenging. This review shows that productivity can be enhanced through new generation catalysts, use of green solvents, and a more efficient reactor technology while the use of tailor-made membrane in appropriate modules holds the promise of low-cost and eco-friendly downstream purification. It is exposed that a membrane-based technology can bring about high degree of process intensification, whereas recovery and reuse of catalysts and alcohol are likely to add to the economy of the process, resulting in sustainable production technology.